THE EFFECT OF BATTALION COMMANDER’S LEADERSHIP STYLE ON READINESS TO CHANGE AMONG SOLDIERS OF INFANTRY BATTALION X IN INDONESIA - Emir Harirachman Rindipati; Zahrotur Rusyda Hinduan (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2021)
The Indonesian Army (TNI AD) is improving its main capabilities to meet the demand of the changing form of armed conflict. As for human capabilities, leadership is still counted as the main capabilities. To develop its capabilities as an organization, TNI AD must focus on its soldiers' readiness to change. Based on the previous research findings and the need to change in TNI AD, research must be conducted to demonstrate the effect of leadership style on TNI AD soldiers' readiness to change This study aims to determine the effect of battalion commander’s leadership style on soldiers’ readiness to change in Xth Infantry Battalion. Data collection using questionnaires has been completed for both variables, the commander's leadership style and soldiers’ readiness to change. The analytical tool used in this study is simple linear regression analysis, correlation test, and t-test using SPSS for windows 23.0. The result showed that the transformational leadership of the Xth Infantry Battalion Commander has positive effects on readiness to change of soldiers from Xth Infantry Battalion. The coefficient determinant demonstrated from this study is 50,2%, meaning that the Xth battalion commander's transformational leadership effect on soldiers' readiness to change is 50,2%. This study is preliminary and has its limitations. However, this study can be developed in many ways for the benefit of the Indonesian Army to change to meet the ever-changing dynamics of armed conflict.